Present laughter : humour at the site of impact in theatre performance - Weitz, Eric (Trinity College (Dublin, Ireland). Department of Drama, 2000)
This dissertation examines the implications for the humorous transaction at its immediate site of impact within mimetic theatre performance, as given to the bodied subjects involved. The thesis establishes its theoretical underpinnings in two general areas, seeking to address the event in its ‘lived-through’ capacity as fluid, unduplicable and denying fair grasp from any single analytic perspective: The thesis builds upon Maurice Merleau-Ponty’s approach to bodied consciousness as the originating perspective for human experience within the fabric of worldly existence. It proceeds to define theatre, humour, and their piggybacking in performance, as transactions in thrall to the intertwining reversibilities which embrace the systems of body/consciousness, subject/world and self/others. Further justifications derive from phenomenological theorists including Mikel Dufrenne, Stanton Gamer, Marvin Carlson, Bruce Wilshire and Bert O. States.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin